2010
DOI: 10.1017/s0033822200045392
|View full text |Cite
|
Sign up to set email alerts
|

High-Precision Radiocarbon Dating of the Construction Phase of Oakbank Crannog, Loch Tay, Perthshire

Abstract: ABSTRACT. Many of the Loch Tay crannogs were built in the Early Iron Age and so calibration of the radiocarbon ages produces very broad calendar age ranges due to the well-documented Hallstatt plateau in the calibration curve. However, the large oak timbers that were used in the construction of some of the crannogs potentially provide a means of improving the precision of the dating through subdividing them into decadal or subdecadal increments, dating them to high precision and wiggle-matching the resulting d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Second, all of the Polynesian Plainware phase dates in Tonga fall within a segment of the radiocarbon calibration curve that is substantially flattened. This is referred to as the “Early Iron Age” or “Hallstatt Plateau” [ 29 ]. When radiocarbon ages between 2650 and 2350 BP are calibrated, they typically incorporate the same 250–300 year time range.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Second, all of the Polynesian Plainware phase dates in Tonga fall within a segment of the radiocarbon calibration curve that is substantially flattened. This is referred to as the “Early Iron Age” or “Hallstatt Plateau” [ 29 ]. When radiocarbon ages between 2650 and 2350 BP are calibrated, they typically incorporate the same 250–300 year time range.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…In few cases, high-precision measurement with 0.1% uncertainties of statistics and scatter has been achieved [16]. Such high-precision measurements were facilitated >2 mg graphite target materials which produce stable ion beam and have long target longevity, in addition to the relatively high C À ionization efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…Applications that attempt to produce precise chronologies in this period are still rare, and those that exist usually exploit the extremely powerful prior information provided by floating tree-ring series. Some tree-ring sequences extend beyond either the start or the end of the plateau and can thus be fixed against steep sections of the curve (Kuzmin et al 2004;Quarta et al 2010), but in other cases, precise dating has been suggested for series that fall entirely within the plateau (Cook et al 2010;Chochorowski et al 2014). Research is also underway to improve our understanding of the detailed structure of the calibration curve in this period (Kromer et al 2010;Suzuki et al 2010;Taylor and Southon 2013;Jacobsson et al 2017).…”
Section: Approach and Objectives Of The Dating Projectmentioning
confidence: 99%